Sintesis Lapisan Tipis Komposit Ni-TiAlN Menggunakan Teknik Elektrodeposisi pada Berbagai Substrat - Muarief Muarief; Esmar Budi; Iwan Sugihartono (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2015)
Composite coating on metal is subjected to improve its wear and corrosion resistances. Electrodeposited Ni-TiAlN composite film using variations of metal or metal alloy type as substrate has been investigated. Variation of substrate type used amount 3 variations that are High Speed Steel (HSS), Brass and Galvanis. On this experiment, the electrolyte composition consist of 0.38 M Ni2SO4.6H2O, 0.17 M NiCl2.6H2O and 0.49 M H3BO3 added with each 6 gr/liter amounts of TiN and AlN powders and Dodecyl Sulfate Sodium (C12H25NaO4S) 0.5 gr/liter as sufraktan. The experiment was performed at electrodeposition current of 3.0 mA for about 15 minutes. The results show that the composite film morphology is different in each substrate. Keywords: Elektrodeposition, Ni-TiAlN composite film, High Speed Steel, Brass, Galvanis.